Xpert MTB/RIF Assay Shortens Airborne Isolation for Hospitalized Patients With Presumptive Tuberculosis in the United States - Lippincott, Christopher K.; Miller, Melissa B.; Popowitch, Elena B.; Hanrahan, Colleen F.; Van Rie, Annelies (Clinical infectious diseases, 2014)
Background. In the United States, individuals with presumptive pulmonary tuberculosis are placed in airborne infection isolation (AII) and assessed by smear microscopy on 3 respiratory specimens collected 8–24 hours apart. Xpert MTB/RIF assay (Xpert) on 1, 2, or 3 specimens may be more efficient for determining AII discontinuation. Methods. This single-center, observational cohort study of inpatients with presumptive pulmonary tuberculosis enrolled adults with 1 or more sputum specimens submitted for smear microscopy. Smear microscopy and Xpert were performed on each sputum specimen. Clinicians were blinded to Xpert results. The primary endpoint was AII duration. Secondary endpoints were laboratory processing time, strategy-based tuberculosis detection, and sensitivity and specificity. Results. Among 207 subjects, the median AII duration was 68.0 hours (interquartile range [IQR], 47.1–97.5) for smear microscopy compared with 20.8 hours (IQR, 16.8–32.0) for the 1-specimen Xpert, 41.2 hours (IQR, 26.6–54.8) for the 2-specimen Xpert, and 54.0 hours (IQR, 43.3–80.0) for the 3-specimen Xpert strategies (P ≤ .004). Median laboratory processing time for smear microscopy was 2.5 times as long as Xpert (P < .001). The 2- and 3-specimen Xpert and smear microscopy strategies captured all 6 tuberculosis cases. The 1-specimen Xpert strategy missed 1 case. No difference was observed between smear microscopy and Xpert in sensitivity or specificity for detection of Mycobacterium tuberculosis. Conclusions. Xpert-based strategies significantly reduced AII duration compared with the smear-based strategy. The 2-specimen Xpert strategy was most efficient in minimizing AII time while identifying all tuberculosis cases among individuals with presumptive tuberculosis in this low-burden setting.